1999
DOI: 10.1148/radiology.212.1.r99jl3619
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Staging of Ovarian Cancer: Comparative Values of Doppler and Conventional US, CT, and MR Imaging Correlated with Surgery and Histopathologic Analysis—Report of the Radiology Diagnostic Oncology Group

Abstract: MR imaging is superior to Doppler US and CT in diagnosis of malignant ovarian masses. There is little variation among conventional US, CT, and MR imaging as regards staging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
108
2
9

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 248 publications
(123 citation statements)
references
References 43 publications
4
108
2
9
Order By: Relevance
“…Similar studies showed that chance of malignancy in such cysts are very low about < 1% [17][18][19][20][21] .…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Similar studies showed that chance of malignancy in such cysts are very low about < 1% [17][18][19][20][21] .…”
Section: Discussionmentioning
confidence: 85%
“…One study indicates that MRI may be superior to CT scan and ultrasound scan, in diagnosing ovarian mass but there is no difference in its' ability to distinguish between benign and malignant diseases 15 . Another study found that TVS has greater sensitivity than CT or MRI in this regard 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Current preoperative assessments have limited predictability in selection of patients suitable for OCR. The sensitivity of CT in identifying patients that OCR can be achieved is around 60-70%, with varying reported specificity between 70% and 100% [17,18]. The main drawbacks of CT imaging is the inability to reliably assess the extent of disease in the supra colic compartment, porta hepatis, miliary disease over bowel mesentery and peritoneum, especially in absence of ascites [8][9][10][11]19].…”
Section: Discussionmentioning
confidence: 99%
“…Bimanual pelvic examination and serum CA-125 levels have failed to allow consistent detection of ovarian malignancy. Because the sensitivities of these techniques are often below 50%, imaging modalities have become indispensable (Jacobs et al, 1989;Taylor et al, 1994;Kurtz et al, 1999;Ferozabadi et al, 2011). Sonography has been shown to be a sensitive, but relatively nonspecific method, leading to unnecessary surgical resection of many benign lesions (Outwater et al, 1995).…”
Section: Introductionmentioning
confidence: 99%